Rekayasa Bahan Bangunan dari Abu Vulkanik sebagai Alternatif Semen Ramah Lingkungan - Edi Priyono; Mettadewi Wong (Jurnal Pengabdian Dian Mandala, 2025)
This study aims to analyze the effect of variations in body angle on propulsion force and water resistance in swimming athletes through a biomechanical approach. The background of the study is based on the importance of movement efficiency in swimming, where a less than optimal body position can increase the drag coefficient, thereby slowing swimming speed. The research method uses a quantitative experimental design involving professional and semi-professional level swimmers. The instruments used include a motion capture system to record body movements, force sensors to measure propulsion and water resistance, and biomechanical software to analyze force vectors and drag coefficients. The results show significant differences in swimming performance based on variations in body angle. At an angle of 0°, the average propulsion force generated is 145.3 N with a drag coefficient of 0.92. At an angle of 15°, the propulsion force increases to 162.7 N with the lowest drag coefficient of 0.78. Meanwhile, at an angle of 30°, the propulsion force decreases to 150.1 N with the drag coefficient again increasing to 0.88. These findings demonstrate that a 15° body angle is the most optimal position because it minimizes water resistance while maximizing propulsion, thereby increasing swimming efficiency. The implications of this study suggest that a biomechanical approach can be used as a reference in planning swimming training programs. In addition to contributing to the development of sports science, the results of this study also have practical benefits for athletes and coaches in developing more effective training strategies. Future research is recommended to expand the sample size and include various swimming styles to strengthen the generalizability of the results.